INTERGROUP CONTACT AVOIDANCE IN INDONESIA - Cahyo Pamungkas (Masyarakat Indonesia, 2016)
The objective of this study is to investigate the relationship between ethno-religious identification and the avoidance of intergroup contact between Muslims and Christians in Ambon and Yogyakarta with considering individual factors. Also, this study aims to fill the gap in literature between studies that emphasize economic andpolitical contestation as the main sources of conflict and studies that focus on prejudice and discrimination as the causes of conflict. Lastly, this study focuses on examining ethnic group conflict theory, which is relevant to the analysis of ethno-religious conflicts in Western countries. The central research question is to what extent is there a relationship between ethno-religious identification among Christians and Muslims in Ambon and Yogyakarta, and avoidance of intergroup contact considering other individual-level determinants and particular intermediate determinants (salience of identity, perceived threats, intergroup contact, religiocentrism, attitudes toward religious plurality, interpretation of sacred writing, perceived discrimination, individual memory of violence, nationalistic attitudes, distrust, and social dominance orientation). I use both qualitative and quantitative methods as approaches to gathering and analysing data to support this study. The data collection methods included surveys, interviews, literature studies, and observations. Surveys were conducted among students at the undergraduate level with aminimum of second year standing from six universities in Ambon and Yogyakarta.Keywords: contact avoidance, ethno-religious identification, perceived-threat, religious pluralism ABSTRAKPenelitian ini bertujuan untuk mengkaji hubungan antara identifikasi etno-religius dan perilaku menghindari interaksi antarkelompok, antara Muslim dan Kristen di Ambon dan Yogyakarta, dengan mempertimbangkan faktor-faktor pada tingkat individu. Selain itu, studi ini juga dimaksudkan untuk mengisi kesenjangan dalam literatur antara studi yang menekankan kontestasi ekonomi dan politik sebagai sumber utama konflik dan studi yang berfokus pada prasangka dan diskriminasi sebagai penyebab konflik. Terakhir, penelitian ini difokuskan pada menguji teori konflik etnis yang relevan dengan analisis konflik etnik-agama di negara-negara Barat pada konteks Asia Tenggara. Pertanyaan penelitian studi ini adalah sejauh mana hubungan antara identifikasi etnikreligius di antara komunitas Muslim dan Kristiani di Ambon dan Yogyakarta dengan perilaku mereka menghindariinteraksi antarkelompok etnik-religius dengan mempertimbangkan faktor-faktor indivdu, seperti perceived threat, religious pluralism, perceived discrimination, dan kontak anatrkelompok serta memori kekerasan. Penelitian ini menggunakan pendekatan mix method untuk mengumpulkan dan menganalisis data. Metode pengumpulan data termasuk survei, wawancara, studi literatur, dan observasi. Survei dilakukan di kalangan mahasiswa tingkatsarjana dengan minimal tahun kedua di enam universitas di Ambon dan Yogyakarta.Kata kunci: perilaku menghindari interaksi, identifikasi etno-religius, perasaan terancam, pluralism keagamaan